2021
DOI: 10.1111/eci.13525
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and pathways related to breast cancer metastasis in an integrated cohort

Abstract: Background Breast cancer is the most common malignant disease in women. Metastasis is the most common cause of death from this cancer. Screening genes related to breast cancer metastasis may help elucidate the mechanisms governing metastasis and identify molecular targets for antimetastatic therapy. The development of advanced algorithms enables us to perform cross‐study analysis to improve the robustness of the results. Materials and methods Ten data sets meeting our criteria for differential expression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Meanwhile, KEGG pathway analysis suggested that the signal pathways including cell cycle, homologous recombination, oocyte meiosis were signi cantly involved. Notably, these pathways have been shown to be related to the cancer's occurrence and development [29][30][31]. Our results suggested that the prognosis of LUSC may be improved by testing the identi ed DEMs and DMGs, and the LUSC development is a complex process involving various genes and proteins.…”
Section: Discussionmentioning
confidence: 70%
“…Meanwhile, KEGG pathway analysis suggested that the signal pathways including cell cycle, homologous recombination, oocyte meiosis were signi cantly involved. Notably, these pathways have been shown to be related to the cancer's occurrence and development [29][30][31]. Our results suggested that the prognosis of LUSC may be improved by testing the identi ed DEMs and DMGs, and the LUSC development is a complex process involving various genes and proteins.…”
Section: Discussionmentioning
confidence: 70%
“…These include Matrix Metallopeptidase 7 (MMP7), transcript factors of YAP1 (one of the most important effectors of the Hippo pathway) and FOXM1, fibroblast growth factor receptor 2 (FGFR2), Eukaryotic initiation factor 3B (EIF3B), Kinesin Family Members (Kif14, Kif4A, Kif23 and Kif2C), Cyclin Dependent Kinase 1 (CDK1), Cell division cycle proteins (CDCA3, CDCA5, CDCA7, CDCA8, CDCA20 and CDC25C) and Check point Kinase 1 (CHEK1). Some of these genes have also been found to be associated with breast cancer metastasis in our previous research [ 25 ].…”
Section: Discussionmentioning
confidence: 94%
“…One study used RNA sequencing to probe the cellular origin and evolution of breast cancer in BRCA1 mutant carriers ( 25 ). Additionally, bioinformatics has reportedly been used to identify differentially expressed genes (DEGs) associated with breast cancer metastasis and provide potential therapeutic targets for metastatic breast cancer ( 26 ). Bioinformatics data combined with imaging findings can also play a crucial role in breast cancer diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%